APPLICATION OF A NEW PREPARATIVE PYROLYSIS TECHNIQUE FOR THE DETERMINATION OF SOURCE-ROCK TYPES AND OIL/SOURCE-ROCK CORRELATIONS - Lafargue E.; Behar F. (My University, 1989)
A new preparative pyrolysis technique enabling the recovery and fractionation (into saturated hydrocarbons, unsaturated hydrocarbons, and aromatic hydrocarbons) of the total C6+ hydrocarbon fraction (instead of the C13+ fraction usually recovered) has been applied to different types of source-rocks. The composition of the C7–C13 hydrocarbon fraction in the pyrolysate, particularly the amount of aromatic hydrocarbons as compared to alkanes, was found to be characteristic of each type of kerogen, with the ratio consistently decreasing in the progression from Type I to Type III kerogens. While the C13+ fraction is useful in kerogen typing, it was found that the C7–C13 hydrocarbon fraction, which represents 40 to 50% of the total recovered pyrolysate, was the most signficant in emphasizing differences between kerogen types, allowing a rapid and precise estimation of the source-rock type. This new technique was applied to potential source-rocks of the Viking Graben, North Sea (Draupne formation, Heather formation, Brent coals, and Dunlin group). In each case, the pyrolysates allowed us to determine whether the organic matter was Type II, Type III, or a mixture of both. Pyrolysis of asphaltenes from crude oils from the various regions was conducted and potential applications of our technique to studies of oil/source-rock correlations were examined.